Characterization and distribution of microplastics in estuarine surface sediments, Kayamkulam estuary, southwest coast of India. (July 2021) - Radhakrishnan, K.; Sivapriya, V.; Rajkumar, A.; Akramkhan, N.; Prakasheswar, P.; Krishnakumar, S.; Hussain, S.M.
Abstract: The present study aims to formulate the characterization and distribution of microplastic in the estuarine surface sediments of Kayamkulam estuary, southwest coast of India. The sediments were dominated by fibre and film shaped microplastic substances. The surface sediments were dominated by <1000 μm microplastics. The composition of microplastics in descending order was as follows: polyester > polypropylene > polyethylene. The distribution of microplastics was significantly higher than that observed in the other study regions, except for Pearl river estuary and Guanabara Bay. The distribution of microplastics was chiefly controlled by estuarine inundating water and the distance of the sampling site from the open sea. Highlights: This study was conducted to assess the distribution of microplastic in estuarine surface sediments, Kayamkulam estuary. The sediments were dominated by fibre and film shape microplastic substances. The composition of the microplastic was showing the following order: polyester > polypropylene > polyethylene.